Resultados do retratamento de pacientes com tuberculose em um Hospital de Referência do Estado de Minas Gerais, no período de 2004 a 2007 - Bruno Horta Andrade (2009)
Objective: To evaluate the efficacy of Brazilian standard regimen fortuberculosis (TB) retreatment and the association between outcomes and drug resistance. Patients and Methods: This was a retrospective cohort study of 144 patients referred to a single reference center for TB in Minas Gerais state, Brazil, between January 2004 and December 2007, for short course retreatment with 2RHZE/4RHE (rifampicin [R], isoniazid [H], pyrazinamide [Z] and ethambutol [E] daily for two months followed by four months of R,H,E). The outcomes of the therapy were defined as success (cure) and unsuccess (relapse, failure and death) and were compared to drug susceptibility test (DST). We looked for possible variables related to unsuccess. Multivariate analysis using the logistic regression method was used to adjust any potential confounders and to estimate odds ratio and its 95% confidence intervals. For independent association the statistical significance was established as p < 0.05.Results: DST availability was poor and late in the course of therapy. Noassociation among demographic variables and outcomes were found.Prevalence of acquired resistance (53,7%) was similar between success and unsuccess groups. Cure was achieved in 58,3%, for the whole sample, and 76,4% when the cases of abandonment were excluded. There were no association between outcomes and DST availability. Alcohol abuse, history of more than five previous treatments and history of abandoning treatment were significantly associated with unsuccess in univariate analysis. In the multivariate logistic regression analysis, resistance to rifampicin (OR: 4.4 CI 95%: 1,12- 17,37; p=0,034) and retreatment due to previous abandonment in the absence of the DST (OR 3,51 CI 95% 1,17-11,06; p=0,003) were significantly associatedwith unsuccess. Conclusions: The efficacy of the Brazilian standard regimen for tuberculosis (TB) retreatment in this series was found to be similar to that reported in the literature. An association between treatment outcome and DST availability was not found. DST had no impact on the predefined outcomes. A proper and clear definition for the practical use of DST need to be established in order to provide more valuable contribution to patients care.